2017
DOI: 10.15171/ijer.2017.11
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and Associated Risk Factors Among College Students

Abstract: Background and aims: Despite the growing epidemic of suicide among college students, the associated risk factors have not been properly understood in developing countries. This study was conducted to estimate the prevalence of suicide ideation and attempt and associated risk factors among university students. Methods: We performed this cross-sectional study in the Hamadan University of Medical Sciences from January to May, 2016, and invited university students to participate voluntarily in the study. The outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 24 publications
0
22
1
5
Order By: Relevance
“…Many studies have shown that inappropriate and excessive use of the Internet to be associated with a variety of psychosocial problems, such as anxiety, 17 depression, 18 insomnia, 19,20 suicidal ideation, 21,22 social phobia, 23 drug abuse, 24 problematic alcohol use, 25 attention deficit hyperactivity disorder, 26 problems with family interactions, 27 increased loneliness, 28 poor general health and emotional well-being 29,30 and demographic and socio-psychological characteristics. 31…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that inappropriate and excessive use of the Internet to be associated with a variety of psychosocial problems, such as anxiety, 17 depression, 18 insomnia, 19,20 suicidal ideation, 21,22 social phobia, 23 drug abuse, 24 problematic alcohol use, 25 attention deficit hyperactivity disorder, 26 problems with family interactions, 27 increased loneliness, 28 poor general health and emotional well-being 29,30 and demographic and socio-psychological characteristics. 31…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, psychiatric distress and smoking have been shown to be associated positively 61,62 . It has been also reported that suicidal thoughts/attempts are strongly associated with smoking (OR = 4.03; 95% CI: 2.65-6.11) 60 .…”
Section: Discussionmentioning
confidence: 92%
“…Drug abusing has been also reported to be associated with a greater number of cigarettes smoked per day 59 . Having high-risk behaviors have been shown to be associated with psychiatric distress and suicidal ideation/attempt 60 . On the other hand, psychiatric distress and smoking have been shown to be associated positively 61,62 .…”
Section: Discussionmentioning
confidence: 99%
“…There are many factors that affect College Students 's mental health. Poverty also has a great influence on people's mental health (Wu, Tao, Zhang et al, 2015;Kwan, Arbour-Nicitopoulos, Duku et al, 2016;Lesani, Mohammadpoorasl, Javadi et al, 2016;Tao, Wu, Zhang et al, 2017;Poorolajal, Ghaleiha, Darvishi et al, 2017). Some strategies have been proposed to treat mental health problems (Becker, Jarrett, Luebbe et al, 2018;Griggs, 2017;Nash, Sixbey, An, et al, 2017).Domestic research on mental health problems of impoverished college students mainly focuses on the demographic characteristics of psychological problems of impoverished college students, the influencing factors of mental health of impoverished college students, and the solutions to mental health problems of impoverished college students (Hu, 2018).…”
Section: College Of Economics and Management Hebei University Ofmentioning
confidence: 99%